PENDEKATAN DERADIKALISASI DAN PERAN PEMERINTAH DAERAH DALAM MENDUKUNG PROGRAM PEMOLISIAN MASAYARAKAT GUNA MENCEGAH PENGARUH TERORISME DI DAERAH - M. ROYANI. A.21211003, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis discusses the problems Deradicalisation approach and Role of Local Governments in Supporting Community Policing Program to Prevent Terrorism in Regional Influence. From the results of research using the method of normative legal research concluded that: 1. Basic Strategy for Combating Terrorism Through Mind Deradicalisation approach departs from the assumption that terrorism started from radicalism. Therefore, efforts to combat terrorism more effectively through a de-radicalization. Its essence is to change the mindset of understanding or considered wrong. You do this by providing a new experience gained not from the battlefield, but of social life through human interaction in an open and inclusive in order to get a true understanding about jihad and terrorism. 2. Relevance Approach to the Development of Community Policing Deradicalisation (Community Policing): Through community policing, law enforcement process can be done in a more